2001
DOI: 10.1161/01.hyp.38.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Wine Polyphenols Decrease Blood Pressure, Improve NO Vasodilatation, and Induce Gene Expression

Abstract: Abstract-The effects of short-term oral administration of red wine polyphenolic compounds on hemodynamic parameters and on vascular reactivity were investigated in rats. Endothelial function and vascular smooth muscle contractility were studied in association with the induction of gene expression in the vascular wall. Rats were treated daily for 7 days by intragastric administration of either 5% glucose or red wine polyphenolic compounds (20 mg/kg). Administration of these compounds produced a progressive decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
149
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(169 citation statements)
references
References 27 publications
17
149
0
3
Order By: Relevance
“…Altogether, these data show that the decreased blood pressure, the reduced post-ischaemic infarct size and the cardiac effects induced by chronic treatment of RWPC could be attributable to an increased production of NO. The present study confirms that short-term administration of RWPC is adequate to produce a sufficient circulating concentration of compounds to induce a decrease in blood pressure and cardiovascular effects as in our previous report (Diebolt et al, 2001). However, the molecular identity of polyphenols responsible for the in vivo effect was still unknown, but they may include oligomeric condensed tannins and anthocyanins (Andriambeloson et al, 1998).…”
Section: Hr Ranaivo Et Alsupporting
confidence: 91%
See 3 more Smart Citations
“…Altogether, these data show that the decreased blood pressure, the reduced post-ischaemic infarct size and the cardiac effects induced by chronic treatment of RWPC could be attributable to an increased production of NO. The present study confirms that short-term administration of RWPC is adequate to produce a sufficient circulating concentration of compounds to induce a decrease in blood pressure and cardiovascular effects as in our previous report (Diebolt et al, 2001). However, the molecular identity of polyphenols responsible for the in vivo effect was still unknown, but they may include oligomeric condensed tannins and anthocyanins (Andriambeloson et al, 1998).…”
Section: Hr Ranaivo Et Alsupporting
confidence: 91%
“…In addition, red wine supplementation of drinking water has been shown to modulate haemostasis and to prevent experimental thrombosis in animals, independently of its alcohol content (Wollny et al, 1999). In a previous work, we have provided evidence for in vivo cardiovascular effects of red wine polyphenolic compounds (RWPC) (Diebolt et al, 2001). Oral administration of RWPC was able to produce a decrease in blood pressure in normotensive rats.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies in animals and humans have suggested that RW and RW polyphenols may improve lipid profiles, reduce platelet aggregation, reduce endothelial dysfunction and improve blood pressure; however, their effect on arterial stiffness remains to be further investigated (Goldberg et al, 1996;Diebolt et al, 2001;Wang et al, 2002;Ralay Ranaivo et al, 2004). To date, one study has investigated the effects of RW polyphenols (7alcohol) on arterial stiffness (Mahmud and Feely, 2002).…”
Section: Introductionmentioning
confidence: 99%